Anti‐CD47 antibody treatment attenuates liver inflammation and fibrosis in experimental non‐alcoholic steatohepatitis models. (15th February 2022) - Gwag, Taesik; Ma, Eric; Zhou, Changcheng; Wang, Shuxia
Abstract: Background & Aims: With the epidemic burden of obesity and metabolic diseases, nonalcoholic fatty liver disease (NAFLD) including steatohepatitis (NASH) has become the most common chronic liver disease in the western world. NASH may progress to cirrhosis and hepatocellular carcinoma. Currently, no treatment is available for NASH. Therefore, finding a therapy for NAFLD/NASH is in urgent need. Previously we have demonstrated that mice lacking CD47 or its ligand thrombospondin1 (TSP1) are protected from obesity‐associated NALFD. This suggests that CD47 blockade might be a novel treatment for obesity‐associated metabolic disease. Thus, in this study, the therapeutic potential of an anti‐CD47 antibody in NAFLD progression was determined. Methods: Both diet‐induced NASH mouse model and human NASH organoid model were utilized in this study. NASH was induced in mice by feeding with diet enriched with fat, fructose and cholesterol (AMLN diet) for 20 weeks and then treated with anti‐CD47 antibody or control IgG for 4 weeks. Body weight, body composition and liver phenotype were analysed. Results: We found that anti‐CD47 antibody treatment did not affect mice body weight, fat mass or liver steatosis. However, liver immune cell infiltration, inflammation and fibrosis were significantly reduced by anti‐CD47 antibody treatment. In vitro data further showed that CD47 blockade prevented hepatic stellate cell activation and NASH progression in a human NASH organoid model. Conclusion: Collectively, these data suggest that anti‐CD47 antibody might be a new therapeutic option for obesity‐associated NASH and liver fibrosis.